Normal and keloid fibroblasts are differentially influenced by IFN‐γ and triamcinolone as well as by their combination. Issue 5 (29th April 2019) - Euler, Teresa; Valesky, Eva M.; Meissner, Markus; Hrgovic, Igor; Kaufmann, Roland; Kippenberger, Stefan; Zöller, Nadja N.
Abstract: Impaired wound healing as well as imbalanced cell proliferation and extracellular matrix synthesis and degeneration can cause aberrant scarring. The most severe impacts of such scarring on patients' lives are stigmatization and physical restriction. Although, a broad variety of combinatorial approaches with, e.g., glucocorticoids, chemotherapeutics, and immunomodulators are used, there is still a high recurrence rate of keloids. The aim of this study was to investigate which influence interferon γ (IFN‐γ, 1.000–10.000 IU/mL) and/or triamcinolone acetonide (TA, 1 μg/mL) have on proliferation, cell viability, collagen type I synthesis, and cytokine secretion in healthy and keloid fibroblasts. It was shown that mono‐treatment with IFN‐γ or TA for 2 days induced a severe reduction of the proliferative potential in both cell species. The combinatory treatment (IFN‐γ plus TA) of keloid fibroblasts enhanced the anti‐proliferative effect of the mono‐treatments, whereas no additional anti‐proliferative effect was observed in normal fibroblasts. Furthermore, we observed that the combinatory treatment regimen reduced the expression of α‐smooth muscle actin (α‐SMA), an actin isotype contributing to cell‐generated mechanical tension, in keloid fibroblasts. In normal fibroblasts, α‐SMA was reduced by the mono‐treatment with IFN‐γ as well as by the combinatory treatment. The analysis of collagen‐type I synthesis revealed that TA did not reduce collagen type I synthesis in normal fibroblasts but in keloid fibroblasts. IFN‐γ reduced in both cell species the collagen type I synthesis. The combination of TA and IFN‐γ intensified the previously observed collagen type I synthesis reduction in keloid fibroblasts. The herein presented data suggest the combinatory application of IFN‐γ and TA as a promising therapy concept for keloids.